Study of DC Breakdown Voltage in Low Pressure Argon and Nitrogen Gases for Several Electrode Gap - Yaseen, Waleed Ibrahim (Al-Nahrain Journal of Science, 2017)
In this paper the breakdown of Argon and Nitrogen in DC electric field are studying at different electrode gaps d. The discharge system consists of two electrodes; Cathode electrode is made from Aluminum with 7cm diameter, whereas Anode electrode made from molybdenum metal with 7 cm diameter. Electrode gap ranges between 2-5 cm. Pressure vacuum varies from 0.08 mbar to 0.2 mbar and DC power 750 W. The breakdown voltage Vb is shown to depend on the product (p.d), for lower values of pressure, p or gap, d. This work represents the investigation of the dependence of the breakdown voltage on the gas pressure and on the distance between electrodes and the type of gas. The minimum value of breakdown voltage increases with increases gap d and this value for Argon gas is lower than Nitrogen gas and from this value can determine pressure and current sputtering, while the discharge current increases with pressure.